Pattern and prevelence of alloimmunization in multiply transfused patients with sickle cell disease in Nigeria. Issue 1 (December 2015) - Kangiwa, Umar; Ibegbulam, Obike; Ocheni, Sunday; Madu, Anazoeze; Mohammed, Ndakosu
Abstract Background and study objectives Blood transfusion is central in the prevention and treatment of certain chronic complications of sickle cell disease. It is indispensible in correcting anaemias as well as in the practice of exchange blood transfusion. These gains are largely limited by formation of allo-antibodies. Several studies demonstrated varying frequencies of allo-immunization in various patient groups. The effect of the racial differences between the donor and recipient pool, which has been subsumed in this study, has continuously created a confounding effect on the results of previous studies. Aim This study was aimed at determining the pattern and frequency of allo-immunization in multiply transfused sickle cell patients, in a racially matched donor and recipient population. Patients and methods This was a cross-sectional case-controlled study involving 80 Nigerian sickle cell disease patients who had received three or more units of packed red cells in the within 4 weeks of the study and 40 controls (who were SCD that had not been transfused in their life time). Antibody screening and identification was done using the Diamed microtyping system. Results Frequency of allo-immunization was determined to be 18.7 % (15/80) among the previously transfused and 5 % (15/120) in all sickle cell disease patients. Auto-antibodies were detected in 1.25 % of the study group and 2.5 % of the control, and all reacted with the Kell and Lutheran blood group antigens. The pattern of allo-antibodies found showed; 46.7 % Rhesus, 40 % Kell, while Lutheran and Duffy 13.3 %, each. Conclusion Sickle cell disease patients are particularly susceptible to development of allo-antibodies despite racial similarities between the donor and recipient population. The most common allo-antibodies are Rhesus, Kell and Lutheran and Duffy respectively in order of decreasing frequency. Development of auto-antibodies seems to be independent of blood transfusion in sickle cell disease with possibly different pathogenetic mechanism. Policy on extended red cell phenotyping for common antigens will reduce allo-immunization among multiply transfused patients.